Palafitas Digitais: comunicação, convergência cultural e relações de poder em Afuá - MIRANDA, Diogo Silva Miranda de (Universidade Federal do Pará, 2015)
This research aims to analyze the communication issues in the Amazon. To do this, I try to understand the social uses that individuals do of different technologies involved in the process. And I also try to understand the power relations that are established at scene. For this exercise, I‟m using Jesús Martín-Barbero‟s (2004) theoretical and methodological aspects, which identifies the mapping like a more open and rigorous perspective of study. This aspects allows the researcher to experience the dynamics of the object. This experience was the key to grasping the reality that must be experienced to finally be understood. In analyzing this contemporary setting, I also seek support in the work of Henry Jenkins (2012) to understand that culture is changing and the different information and communication technologies (ICTs) are organizing to provide individuals an experience unlike interaction society. However, one thing must keep in mind that not all participate in the same manner. Here, Michell Foucault (1996, 2008) help to understand the analytical issues of power in society, how manifest disputes in small stocks and how individuals perform small forms of domination. From these questions we can say that Amazon has a multifaceted context, where the differences are inscribed in each part of its territory. Afua is an example of the complexity that exists in the region. Located at the Marajo‟s archipelago, in the brasilian Amazon, the "Venice of Marajó" (as the city is called by its residents) has its streets, houses and high buildings on stilts that support the entire city on the rivers. In this particular place, the web became popular a few years ago by the signal of mobile phones and provided a new scenario of interaction among its residents. But their success is strongly linked to the importance that the radios have the articulation of social relations that community. So we can see how each form of use of ICTs is linked to experiences that take place in society. In this sense, thinking of communication in the Amazon is an exercise that requires looking at the communicative nature of social events (FRANÇA, 2001). These developments reflect specific contexts, that particularize the place where they happen. It is these contexts that enable the particular practices of appropriation and the different uses of social media. They make the experience of individuals a unique and singular event and that allow us to understand the extent of the communication process that goes beyond simple social interaction.